Partisipasi Publik Deliberatif Berbasis Website Dalam Perumusan Kebijakan Daerah (Studi Kasus di Dinas Perizinan Pemerintah Kabupaten Sleman Tahun 2014) - Fatchuriza, Muhammad; Nurmandi, Achmad (Journal of Governance and Public Policy, 2015)
Participation is one of the important elements that must be considered in the policy, this participation is a form ofpolitical participation of the people is very important in order to create good governance. Therefore, the implementationof public participation in policy formation should be regulated more clearly. Sleman District Government consistentlymanage the aspirations of the people with technology, information, and communication or so-called e-government.The purpose of this study was (1) Analyze matters relating to the implementation of deliberative public participationbased websites (2) Analyzing the supporting factors and obstacles in the implementation of web-based deliberativepublic participation in Local Government Licensing Office Sleman 2014. This research pressure was on thefield research and the method used in this study was descriptive analysis both qualitative and quantitative. The dataparticularly obtained from respondent by purposive sampling technique, based on the questionnaire and interview asprimary data, and completed with secondary data. Results of the study, the research obtained showed that theimplementation of public participation in policy formulation Sleman has been running well and were level Consultation(consultation), and there are stages Inclusion or participation. The driving factors: the institutional, kontinyunitas,facilities and infrastructure memadahi. Inhibiting factors: the complaint of data is not accurate, human limitations andhuman error.It can be concluded that the method of public participation in the formulation of regional policies, new isan obligation that must be implemented by the government, because of the demands of decentralization in localautonomy government wants a role alongside other stakeholders in the formulation of regional policies. Suggestionssubmitted so that in the future the government is obliged to increase the facilities of the level of public consultationinto the degree of force (Degree of Citizen Power).